The Transformation of Moses: Reading Exodus 4:24-26 in Light of Exodus 2:3-10 - Hare, Laura (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2026)
This paper examines Exodus 4:24-26 in its context in order to determine the function and meaning of the passage. The paper argues that Exod 4:24-26 acts as a parallel to Exod 2:3-10. In Exod 2:3-10, Moses underwent a life-threatening experience and transformed into an Egyptian. In Exod 4:24-26, he undergoes another life-threatening experience, with two results: Moses is transformed back into a Hebrew, and he transitions into adulthood, making him an appropriate leader for the Hebrews.